Trifocal versus Pentafocal bone transport in segmental tibial defects: a matched comparative analysis for posttraumatic osteomyelitis treatment - Yimurang Hamiti; Patiman Abudureyimu; Gang Lyu; Aihemaitijiang Yusufu; Maimaiaili Yushan (BMC Musculoskeletal Disorders, 2024)
Abstract Purpose The objective of this study was to evaluate and compare the effectiveness and clinical results of trifocal bone transport (TBT) and pentafocal bone transport (PBT) in treating distal tibial defects > 6 cm resulting from posttraumatic osteomyelitis, highlighting the potential advantages and challenges of each method. Methods A retrospective assessment was conducted on an overall population of 46 eligible patients with distal tibial defects > 6 cm who received treatment between January 2015 and January 2019. Propensity score analysis was used to pair 10 patients who received TBT with 10 patients who received PBT. The outcomes assessed included demographic information, external fixation time (EFT), external fixation index (EFI), bone and functional outcomes assessed using the Association for the Study and Application of the Method of Ilizarov (ASAMI) scoring system, and postoperative complications evaluated using the Paley classification. Results The demographic and baseline data of the two groups were comparable. Following radical debridement, the average tibial defect was 7.02 ± 0.68 cm. The mean EFT was significantly shorter in the PBT group (130.9 ± 16.0 days) compared to the TBT group (297.3 ± 14.3 days). Similarly, the EFI was lower in the PBT group (20.67 ± 2.75 days/cm) than in the TBT group (35.86 ± 3.69 days/cm). Both groups exhibited satisfactory postoperative bone and functional results. Pin site infection was the most common complication and the rates were significantly different between the groups, with the PBT group demonstrating a higher incidence. Conclusion Both TBT and PBT effectively treat posttraumatic tibial defects greater than 6 cm, with PBT offering more efficient bone regeneration. However, PBT is associated with a higher rate of pin site infections, highlighting the importance of careful management in these complex procedures and emphasizing the need for expert surgical execution and tailored treatment approaches in orthopedic reconstructive surgery.